Acute flaccid myelitis: an emerging clinical entity. (12th November 2018) - Okumura, Akihisa; Mori, Harushi
Abstract : This commentary is on the original article by Gordon‐Lipkin et al. on pages366–375 and the case series by Kirolos et al. on pages376–380 of this issue.